PERANAN LEMBAGA SWADAYA MASYARAKAT (LSM) DALAM MENUNJANG PEMBANGUNAN DESA DI KECAMATAN PAMONA SELATAN KABUPATEN POSO - TALIMBA, VINDA MARGARETHA; DENGO, SALMIN; RURU, JOORIE MARHAEN (JURNAL ADMINISTRASI PUBLIK, 2015)
AbstractThe existence of NGOs in the village is expected to play a role to support ruraldevelopment both direct and indirect, indirectly through the implementation of their ownprograms as well as directly through participation or involvement in rural developmentactivities undertaken by the village government. The role of NGOs in supporting ruraldevelopment can also be realized in their role as the aspirations channel of thecommunity, as a media that connect the communication between the government andthe community, as a media for mobilizing community participation in development, andas a public controller of the development in the village. Therefore, this study wasconducted to the extent of the role of NGOs in supporting rural development in thedistrict of South Pamona.This study used qualitative methods. Sources of data or informants drawn fromgovernment districts, village government, community organizations or LPMD in thevillage, leaders or community members, and administrators or managers of the NGO inthe sub-district / village, entirely as many as 13 people. Data collection is using interviewtechniques. While the analysis of the data using qualitative techniques.The results showed: (1) NGOs that exist and operating in South Pamona subdistricthas been proved in supporting rural development through programs andactivities that they are perceived to support the progress of the village, and providebenefits to rural communities, especially the target of the NGO itself. (2) The role ofNGOs in supporting rural development through their role as as the aspirations channelof the community, as the communication bridge between government and community, asa media for mobilizing community participation in development, and and as a publiccontroller of the development in the village, it can be realized but generally still limitedto their organization or they only focus for the members or target of the NGO itself. Theresults of these studies may lead to the conclusion that the existence of NGOs operatingin the community or village level, can really play a useful role in supporting ruraldevelopment.Based on the study results, it is suggested that the implementation of programsand activities must be adapted to local conditions, so that NGOs should coordinate withlocal authorities in this case can be the head of district or village in the preparation ofthe program implementation.Keyword(s): The role of NGO, Rural Development